A brief review of severe asthma / Muhammad Amin Ibrahim, Ahmad Izuanuddin Ismail and Mohammed Fauzi Abdul Rani - Ibrahim, Muhammad Amin; Ismail, Ahmad Izuanuddin; Abdul Rani, Mohammed Fauzi (Faculty of Medicine, 2021)
Severe asthma describes an asthma condition that requires a substantial amount of inhaled corticosteroid and bronchodilators to keep it under control including the frequent additional need for oral steroid to avoid exacerbations. The incidence of severe asthma in Malaysia is unknown but data elsewhere shows that it is around 5 to 10 % of asthmatics. This category of asthmatic patients has considerable morbidity, is disproportionate cost-wise to the number of sufferers and requires specialised and focused care. The management of severe asthma should be undertaken at a severe asthma clinic led by a physician with a special interest in its management. The diagnosis needs confirmation, comorbidities identified and triggering factors addressed. Inhaler technique and compliance are major contributing issues and must be addressed at all consultation opportunities. Once the diagnosis of severe asthma is confirmed, the disease needs phenotyping to plan for the most appropriate treatment, termed as a personalised approach to severe asthma care. The advances in biologics have changed the landscape of treatment of this disease but in Malaysia especially, there are many limitations namely the cost. This article briefly explores the current understanding of severe asthma, the assessment including phenotyping and possible treatment options.